A47 Quantitative trait locus analysis in yeast: identifying candidate therapeutic targets for huntington's disease. (September 2018) - Alfonso-Núñez, Mónica; Louis, Edward J; Giorgini, Flaviano
Abstract : Background: Huntington's disease (HD) is caused by the expansion of a CAG trinucleotide repeat in the huntingtin (HTT) gene. Beyond a critical disease-causing threshold, the number of repeats correlates strongly with severity of disease, though a significant proportion of variation in disease presentation is due to genetic modifiers. Saccharomyces cerevisiae has been successfully used in the past to identify modifiers of mutant HTT toxicity, and thus will serve as a robust model for the identification of novel genetic variants by quantitative trait locus (QTL) analysis. Aims: This work seeks to establish a novel QTL analysis platform in yeast for the identification of genetic modifiers of mutant HTT toxicity. Methods: We screened 14 natural yeast isolates containing most of the genetic variation of the species (1–2 SNPs per 100 base pairs) for several phenotypes (e.g. growth, mutant HTT expression and aggregation) to identify ideal parental strains with extreme phenotypes for QTL analysis. Results: The strain HN16 exhibited severe growth defects upon expression of a mutant HTT fragment tagged with GFP (HTT103Q), reminiscent of the toxicity observed in the laboratory strain BY4741. This toxicity correlated with the presence of mutant HTT aggregates identified by fluorescence microscopy. On the other hand, the HN10 strain was resistant to HTT103Q toxicity and exhibited diffuse cytoplasmic localization of this protein. Analysis of GFP fluorescence in these strains indicates that the reduced toxicity in the HN10 strain is not due to decreased expression of the mutant HTT construct. Conclusions: This work has characterized ideal parental strains for QTL analysis of HTT103Q toxicity modifiers. The descendants of intercrosses will be analysed for differences in segregation of SNPs between resistant and sensitive strains to map possible modifier genes. Candidate genes will be further analysed in yeast and validated in more physiologically relevant models of HD.